ETIOLOGY OF SEASONAL INCREASING OF ENTEROVIRAL INFECTION INCIDENCE IN ARKHANGELSK OBLAST - L. A. Shishko (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. The etiology of seasonal increasing of enteroviral infection incidence in Arkhangelsk oblast in 2008–2011 has been studied. The ECHO 6, ECHO 9 and ECHO 30 viruses were isolated and identified from patients with enteroviral infection in this period. The highest enteroviral infection incidence rate in Arkhangelsk oblast which was 5,1 times higher in compare with average country index was registered in 2008. It was proved by the virological and molecular biological methods that the main etiological agent caused enteroviral meningitis cases in the seasonal outbreak in 2008 was ECHO 30 virus which was very similar to the ECHO 30 strain identified in the Veliky Novgorod in 2008. In 2009 from patients in enteroviral meningitis epidemic focus the ECHO 9 viruses were isolated. These viruses were similar to the ECHO 9 strains circulated in Russia in 2009. It was established that in the period of seasonal increasing of enteroviral infection in Arkhangelsk oblast in 2010–2011 in general circulated ECHO 6 viruses which clustered in 3 separate phylogenetic groups. Viruses ECHO 6 detected in Arkhangelsk oblast in 2011 were different from viruses identified in 2010. Results of the study confirm that monitoring of viruses in case of enteroviral infection remains the one of the important types of additional measures in the frame of Global Program of poliomyelitis eradication. This monitoring is absolutely necessary to define characteristics of epidemic process of enteroviral infection.